2014
DOI: 10.1007/s10995-014-1488-x
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Field-Based Professionals in a Qualitative Assessment of Barriers and Positive Contributors to Breastfeeding Using the Social Ecological Model

Abstract: Despite broad recognition of benefits associated with breastfeeding, rates in the United States continue to be below targets established by Healthy People 2020, especially for economically disadvantaged women. This study engaged field-based professionals through a focus group process to collect perceptions on factors that determine a woman's decision to breastfeed. Field-based professionals participated in one of six focus groups. Following the social ecological model (SEM), focus group questions addressed bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…Understanding the pathway between workplace environments and breastfeeding duration is necessary to design effective interventions. This study is grounded in the social‐ecological model that is adapted to fit health promotion activities due to widespread consensus that individual behaviors are influenced by social environments . The social‐ecological model also states that community and social environmental factors can interact with individual factors, such as breastfeeding intentions and self‐efficacy, to produce a desired outcome (ie, breastfeeding duration)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the pathway between workplace environments and breastfeeding duration is necessary to design effective interventions. This study is grounded in the social‐ecological model that is adapted to fit health promotion activities due to widespread consensus that individual behaviors are influenced by social environments . The social‐ecological model also states that community and social environmental factors can interact with individual factors, such as breastfeeding intentions and self‐efficacy, to produce a desired outcome (ie, breastfeeding duration)…”
Section: Introductionmentioning
confidence: 99%
“…This study is grounded in the social-ecological model that is adapted to fit health promotion activities due to widespread consensus that individual behaviors are influenced by social environments. 13 The social-ecological model 14 also states that community and social environmental factors can interact with individual factors, such as breastfeeding intentions and self-efficacy, to produce a desired outcome (ie, breastfeeding duration). 15 Several studies have demonstrated a relationship between breastfeeding intention, self-efficacy, and breastfeeding duration.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significant benefits of breastfeeding (2)(3)(4), education and support are common in and out of the hospital. However, there are many prenatal, medical, hospital, societal and sociocultural barriers that make it more difficult for mothers to actively meet the recommended goals for breastfeeding (5,6). One potential barrier to breastfeeding that has been identified is the use of artificial teats (7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…As ecological models have demonstrated [Dunn, Kalich, Henning, & Fedrizzi, 2015;Vitzthum & Aguayo, 1998], a nested set of environments provides the context in which infant feeding decisions occur. These nested contexts provide the backdrop to the pre-action and action phases that follow, informing and moderating the ongoing decision-making and behaviors going forward in time.…”
Section: Pre-action Phase 1: the Accumulation And Interaction Of Riskmentioning
confidence: 99%